2019
DOI: 10.23888/pavlovj201927135-40
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence rate of Helicobacter pylori infection among population of Ryazan region

Abstract: Aim. Determination of the prevalence of Helicobacter pylori (H. pylori) infection among the population of the Ryazan region. Materials and Methods. 833 individuals (809 adults and 24 children) were examined for presence of IgG class antibodies using the enzyme immunoassay (2017-2018). The criteria for inclusion into the study were: a desire of a patient to undergo examination for the presence of antibodies to H. pylori in blood. Criteria for exclusion: past treatment for helicobacteriosis. The presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A serology‐based study that conducted on healthy volunteers in Ryazan in central Russia (2017‐2018) revealed IgG positivity (using IMMULITE 2000, Germany) in 65.6% of the adults and 20.8% of the children not treated previously for H pylori 5 …”
Section: Helicobacter Pylori Prevalence Worldwidementioning
confidence: 99%
“…A serology‐based study that conducted on healthy volunteers in Ryazan in central Russia (2017‐2018) revealed IgG positivity (using IMMULITE 2000, Germany) in 65.6% of the adults and 20.8% of the children not treated previously for H pylori 5 …”
Section: Helicobacter Pylori Prevalence Worldwidementioning
confidence: 99%